Strengths and vulnerabilities: Comparing post-9/11 U.S. veterans' and non-veterans' perceptions of health and broader well-being. (September 2022) - Vogt, Dawne; Borowski, Shelby; Maguen, Shira; Blosnich, John R.; Hoffmire, Claire A.; Bernhard, Paul A.; Iverson, Katherine M.; Schneiderman, Aaron
Abstract: Background: Prior research has examined how the post-military health and well-being of both the larger veteran population and earlier veteran cohorts differs from non-veterans. However, no study has yet to provide a holistic examination of how the health, vocational, financial, and social well-being of the newest generation of post-9/11 U.S. military veterans compares with their non-veteran peers. This is a significant oversight, as accurate knowledge of the strengths and vulnerabilities of post-9/11 veterans is required to ensure that the needs of this population are adequately addressed, as well as to counter inaccurate veteran stereotypes. Methods: Post-9/11 U.S. veterans' (N = 15, 160) and non-veterans' (N = 4, 533) reported on their health and broader well-being as part of a confidential web-based survey in 2018. Participants were drawn from probability-based sampling frames, and sex-stratified weighted logistic regressions were conducted to examine differences in veterans' and non-veterans' reports of health, vocational, financial, and social outcomes. Results: Although both men and women post-9/11 veterans endorsed poorer health status than non-veterans, they reported greater engagement in a number of positive health behaviors (healthy eating and exercise) and were more likely to indicate having access to health care. Veterans also endorsed greater social well-being than non-veterans on several outcomes, whereas few differences were observed in vocational and financial well-being. Conclusion: Despite their greater vulnerability to experiencing health conditions, the newest generation of post-9/11 U.S. veterans report experiencing similar or better outcomes than non-veterans in many aspects of their lives. Findings underscore the value of examining a wider range of health and well-being outcomes in veteran research and highlight a number of important directions for intervention, public health education, policy, and research related to the reintegration of military veterans within broader civilian society. Highlights: Results revealed unique strengths for post-9/11 U.S. veterans compared to non-veterans. Veterans reported poorer health status but more positive health behaviors. Veterans endorsed better social well-being on some outcomes. Results highlight the value of assessing multiple aspects of veterans' health and well-being. Findings can be used to correct inaccurate stereotypes about U.S. veterans.